The Validity of Marriage Registration in the Customary Viewpoint Indonesia - Puspa Melati; Runtung; Siregar, Mahmul; Zulfi Chairi; Windha; Faradila Yulistari; Lesly Saviera; Saddam Shauqi; Hilbertus Sumplisius M. Wau (Mahadi: Indonesia Journal of Law, 2025)
This study explores the validity of marriage registration according to customary law in Indonesia and its relationship with national legislation. Marriage registration is a crucial element of the Indonesian legal system, as stipulated in Law Number 1 of 1974 concerning Marriage, which aims to provide legal certainty, ensure the legal status of children, and protect the civil rights of couples. However, many indigenous communities still hold fast to the tradition that traditional marriage ceremonies are sufficient to legitimize a marriage without requiring official registration. This study found that although customary law recognizes the validity of marriages through traditional rituals, the neglect of official registration with state institutions has legal consequences, such as unclear legal status for spouses and children in inheritance and population administration matters. This research underscores the need for policy integration between customary law and national law to ensure that the rights of indigenous communities remain protected without neglecting formal legal requirements. Potential solutions include public education and simplifying registration procedures to make them more user-friendly for Indigenous peoples.